Dampak Gaya Kepemimpinan Otoriter terhadap Motivasi Kerja dan Produktivitas Karyawan - Seger Santoso; Tanti Sugiharti; Eri Kusnanto (Fakultas Ekonomi Universitas 45 Surabaya, 2025)
Leadership is a critical factor in determining organizational success, particularly in enhancing employee motivation and performance. This study analyzes the impact of authoritarian leadership on employee motivation and productivity across various organizational settings. The research method used is a literature review, examining various sources from academic journals, books, and relevant scholarly articles. The findings indicate that authoritarian leadership, characterized by strict control and centralized decision-making, has both positive and negative impacts. In certain situations, such as crises, authoritarian leadership can increase efficiency and discipline, as decisions can be made quickly and directed effectively. However, in the long term, this style tends to decrease intrinsic motivation, creativity, and employee job satisfaction, potentially affecting overall productivity. Based on these findings, it is recommended that leaders consider balancing control and empowerment, as well as adapting their leadership style to the organizational context and culture, to achieve optimal results.